Just put in the value known for x into the x variable, and solve for y...
y = 2(-3) + 5 = -1
y = 2(-2) + 5 = 1
y = 2(-1) + 5 = 3
y = 2(0) + 5 = 5
y = 2(1) + 5 = 7
y = 2(2) + 5 = 9
y = 2(3) + 5 = 11
X = -3, -2, -1, 0, 1, 2, 3
Y = -1, 1, 3, 5, 7, 9, 11
2006-12-06 04:10:24
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
X -3 -2 -1 0 1 2 3
Y -1 1 3 5 7 9 11
2006-12-06 06:58:08
·
answer #2
·
answered by Sophie B 2
·
0⤊
0⤋
X -3 -2 -1 0 1 2 3
Y -1 1 3 5 7 9 11
₢
2006-12-06 04:16:39
·
answer #3
·
answered by Luiz S 7
·
0⤊
0⤋
x=-3,y=-1
x=-2,y=1
x=-1,y=3
x=0,y=5
x=1,y=7
x=2,y=9
x=3,y=11
Jus replace the value of x given in the equation..
e.g,x=3,
y=2*3+5=11..do the rest..its interesting..
2006-12-06 04:28:49
·
answer #4
·
answered by lUnJ@ 3
·
0⤊
0⤋
This is easy to do, just double each number in the list, then add 5 to it. (each will be two more than the previous one...)
2006-12-06 04:07:58
·
answer #5
·
answered by moto 3
·
0⤊
0⤋